A preliminary annotated bibliography of materials on Sino-Philippine relations available in selected libraries in Metro Manila, 1975-1984 - Zhou Kangmei, 1951- (Institute of Library Science, University of the Philippines Diliman, 1986)
The purpose of this study is to conduct a preliminary survey of materials on Sino-Philippine relations available in selected libraries in Metro Manila from 1975 to 1984 and compile an annotated list of these materials to facilitate their use and help the researchers who are conducting literature searches on the subject.